Improvements in protective measures in factories with acetylene hydrochlorination and ethylene oxychlorination techniques declined risk assessment levels and affected liver health status - Dong, Yiwen; Wang, Xingang; Hu, Weijiang; Bian, Hongying; Wang, Xin; Kang, Ning; Han, Feng; Zhang, Siyu; Ye, Meng (Frontiers in Public Health, 2022)
Techniques of acetylene hydrochlorination and ethylene oxychlorination were two most common methods to produce vinyl chloride monomer (VCM), which has been linked to liver impairment, hepatocellular carcinoma (HCC) and angiosarcoma of liver (ASL) under the occupational setting. However, whether and how these impairment could be effectively improved from the root causes at workplaces have been unknown yet. This study aimed to evaluate whether improvement on protective measures in factories of Y(408 subjects) and Z (349 ones) could play an influential impact on alleviation to liver impairment by comparing risk assessment levels under several semi-quantitative models and results from liver ultrasound detection and liver function tests before and after the improvement. Importantly, significant differences toward constituent ratio involved in parameters among age, length of employment, weekly exposure time, smoking status, alcohol consumption and sleeping quality were found between Y and Z before improvement took place in 2020 (P<0.05 or P<0.001), and population distribution on gender between Y and Z was in largely homogeneity and different in age and length of employment. CSTE referred to ore breaking, acetylene generation, steam stripping, outward processing, welding maintenance were disqualified in 2020 as compared to OEL and were declined to meet OEL requirements by 2021. Further, a negative correction of fresh air requirement and ventilation air changing rate with ambient concentration toward hazards in Y were stronger in 2021 than it was in 2020. Significant differences of risk levels in Y between 2020 and 2021 were found as ore breaking, acetylene generation, steam stripping, outward processing, VCM polymerization, welding and repairing, decreased to relatively lower risk levels in 2021 from original ones in 2020 only under semi-quantitative comprehensive index model. Abnormal rates toward other hepatic symptoms decreased in majority positions after the improvement as referred to alterations of ALT, AST and GGT. Overall, the effect of improvement on protective measures effectively reduced positions’ risk assessment levels through ventilation enhancement and airtight strengthen, which further affected abnormal rates toward other hepatic symptoms and alterations of ALT, AST and GGT were much more significant in Y than effect in Z.